Problem determinacji aksjologicznej stosowania technologii informacyjno-komunikacyjnych w warunkach przejścia do nowego paradygmatu edukacyjnego = Problem of the axiological principles of application of information and communication technologies in the transition to a new educational paradigm - Loboda, Svitlana; Plyska, Yuriy (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article considers the axiological principles of the application of information and communication technologies in the transition to a new educational paradigm. It has been theoretically acknowledged that information and communication technologies today are a necessary leading component of the educational process, which, as a result, forms not only the educational space as a whole, but, importantly, the personality of the future specialist.
Keywords: aksjologia; technologie informacyjno-komunikacyjne; treści medialne; osobowość nauczyciela; values; axiology; information and communication technologies; media content; personality of the future educator